Complement Receptors C5aR and C5L2 Are Associated with Metabolic Profile, Sex Hormones, and Liver Enzymes in Obese Women Pre- and Postbariatric Surgery. (26th March 2014) - Rezvani, Reza; Smith, Jessica; Lapointe, Marc; Marceau, Picard; Tchernof, Andre; Cianflone, Katherine
Abstract : Objective . Obesity is associated with metabolic dysfunction with sex differences and chronic, low-grade inflammation. We proposed that hepatic expression of immune complement C3 related receptors (C3aR, C5aR, and C5L2) would be associated with pre- or postmenopausal status and metabolic profile in severely obese women. We hypothesized that C5L2/C5aR ratio, potentially influencing the ASP/C5L2 metabolic versus C5a/C5aR immune response, would predict metabolic profiles after weight loss surgery. Materials and Methods . Fasting plasma (hormone, lipid, and enzyme analysis) and liver biopsies (RT-PCR gene expression) were obtained from 91 women during surgery. Results . Hepatic C5L2 mRNA expression was elevated in pre- versus postmenopausal women (P < 0.01 ) and correlated positively with circulating estradiol, estrone, ApoB, ApoA1, ApoA1/B, waist circumference, age, and LDL-C (allP < 0.05 ). While plasma ASP was lower in pre- versus postmenopausal women (P < 0.01 ), the hepatic C5L2/C5aR mRNA ratio was increased (P < 0.001 ) and correlated positively with estrone (P < 0.01 ) and estradiol (P < 0.001 ) and negatively with circulating ApoB and liver enzymes ALT, AST, and GGT (allP < 0.05 ). Over 12 months postoperatively, liver enzymes in low C5L2/C5aR mRNA ratio group remained higher (ALP and ALT, P < 0.05, AST and GGT, P < 0.001 2-way-ANOVA). Conclusion . C5L2-C5aR association with other mediators including estrogens may contribute to hepatic metabolic and inflammatory function.